Dietary diversity and opportunistic infections among adults living with human immunodeficiency virus on antiretroviral therapy in Kumasi metropolis; a facility-based cross-sectional study - Charles Apprey; Hammond Yaw Addae; Monica Osei; Irene Danquah; Reginald Annan (BMC Infectious Diseases)
Abstract Background Despite advances in antiretroviral therapy (ART), people living with human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS) continue to face heightened susceptibility to opportunistic infections (OIs). Adequate nutrition remains an essential factor that positively influences disease progression and the occurrence of OIs. In Ghana, no study has evaluated the association between dietary diversity and OI occurrence among adults with HIV. This study aimed to evaluate the association between dietary diversity and the presence of OIs among HIV-positive adults receiving ART. Methods A facility-based cross-sectional study was conducted among 291 HIV-positive adults receiving ART from February 2023 to April 2023 at Kumasi South Hospital, Ghana. The study participants were selected using a convenient sampling method. A pre-tested questionnaire and review of electronic health records were used to collect sociodemographic, nutritional and clinical data. Binary logistic regression analyses were conducted to identify variables significantly associated with the study outcome and hierarchical multivariable logistic regression was used to evaluate the association between dietary diversity and the occurrence of OIs while controlling for confounders at p-value < 0.05. Results The mean age and dietary diversity were 46.2 ± 10.9 years and 4.0 (IQR: 3.0 to 6.0) food groups, respectively. Out of 291 respondents, 152 (52.2%) had inadequate dietary diversity and 39 (13.4%) had at least one OI. The respondents with inadequate dietary diversity were three times more likely to have an OI than their peers with adequate dietary diversity [AOR 3.03, (95% CI: 1.20 to 7.64), p = 0.019]. Conclusion This study revealed that inadequate dietary diversity is a significant nutritional problem and dietary diversity was associated with the presence of OIs among PLWHA on ART at the study site. Hence, there is the need to enhance the intake of diversified diets based on locally available foods. This could decrease the occurrence of OIs and eventually reduce HIV-related morbidity/mortality.